Immunohistochemical Expression of TGF-β1 and Osteonectin in engineered and Ca(OH)2-repaired human pulp tissues - Luiz Alexandre CHISINI; Marcus Cristian Muniz CONDE; Jose Carlos Bernedo ALCÁZAR; Adriana Fernandes da SILVA; Jacques Eduardo NÖR; Sandra Beatriz Chaves TARQUINIO; Flávio Fernando DEMARCO
Abstract The aim of the present study was to evaluate the expression of transforming growth factor-β1 (TGF-β1) and osteonectin (ON) in pulp-like tissues developed by tissue engineering and to compare it with the expression of these proteins in pulps treated with Ca(OH)2 therapy. Tooth slices were obtained from non-carious human third molars under sterile procedures. The residual periodontal and pulp soft tissues were removed. Empty pulp spaces of the tooth slice were filled with sodium chloride particles (250-425 µm). PLLA solubilized in 5% chloroform was applied over the salt particles. The tooth slice/scaffold (TS/S) set was stored overnight and then rinsed thoroughly to wash out the salt. Scaffolds were previously sterilized with ethanol (100-70°) and washed with phosphate-buffered saline (PBS). TS/S was treated with 10% EDTA and seeded with dental pulp stem cells (DPSC). Then, TS/S was implanted into the dorsum of immunodeficient mice for 28 days. Human third molars previously treated with Ca(OH)2 for 90 days were also evaluated. Samples were prepared and submitted to histological and immunohistochemical (with anti-TGF-β1, 1:100 and anti-ON, 1:350) analyses. After 28 days, TS/S showed morphological characteristics similar to those observed in dental pulp treated with Ca(OH)2. Ca(OH)2-treated pulps showed the usual repaired pulp characteristics. In TS/S, newly formed tissues and pre-dentin was colored, which elucidated the expression of TGF-β1 and ON. Immunohistochemistry staining of Ca(OH)2-treated pulps showed the same expression patterns. The extracellular matrix displayed a fibrillar pattern under both conditions. Regenerative events in the pulp seem to follow a similar pattern of TGF-β1 and ON expression as the repair processes.